2020
DOI: 10.2174/1874944502013010723
|View full text |Cite
|
Sign up to set email alerts
|

Significant Association between Physical Performance and Inflammatory Biomarkers in Older Adults with Frailty in Rural Thailand

Abstract: Background: The etiology of frailty is complex and incompletely understood, and is associated with alterations in the immune system, resulting in chronic low-grade inflammation. However, few studies have explored the inflammatory biomarkers related to physical performance in the elderly. Methods: We evaluated the prevalence of frailty with a cross-sectional study among older adults in rural communities in Thailand (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
2
0
0
Order By: Relevance
“…These findings corroborate the literature, demonstrating that multicomponent exercise programs for the elderly, such as FT, are able to provide improvements in physical performance, delay frailty and decrease inflammation, including those who are frail. 23 This evidence helps to explain the reduction of pain and its association with the improvement in physical capacity observed in the present study.…”
Section: Discussionsupporting
confidence: 77%
“…These findings corroborate the literature, demonstrating that multicomponent exercise programs for the elderly, such as FT, are able to provide improvements in physical performance, delay frailty and decrease inflammation, including those who are frail. 23 This evidence helps to explain the reduction of pain and its association with the improvement in physical capacity observed in the present study.…”
Section: Discussionsupporting
confidence: 77%
“…Almost half of the participants had a BMI that placed them in the obesity 1 group (40.0%). Marfiani et al [15] reported 18.4% obesity for the same age group as our study, and Sadjapong et al [16] reported 14.5% obesity in Thailand. Nangoy and Kumala [6] explored the effect of physical activity on fat mass, finding that subjects with low physical activity had a 2.58-fold greater risk of excess fat mass than those with high physical activity.…”
Section: Participant Characteristicssupporting
confidence: 78%